Bank funding risk, reference rates, and credit supply - Harry Cooperman; Darrell Duffie; Stephan Luck; Zachry Wang; Yilin Yang (Federal Reserve Bank of New York, 2023)
Corporate credit lines are drawn more heavily when funding markets are more stressed. This covariance elevates expected bank funding costs. We show that credit supply is dampened by the associated debtoverhang cost to bank shareholders. Until 2022, this impact was reduced by linking the interest paid on lines to credit-sensitive reference rates such as LIBOR. We show that transition to risk-free reference rates may exacerbate this friction. The adverse impact on credit supply is offset if drawdowns are expected to be left on deposit at the same bank, which happened at some of the largest banks during the COVID recession.
Keywords: G00; G01; G02; G20; G21; E4; E43; 330; bank funding risk; credit supply; reference rates; credit lines; London Interbank Offered Rate (LIBOR); Secured Overnight Financing Rate (SOFR)